2020
DOI: 10.1021/acs.organomet.0c00646
|View full text |Cite
|
Sign up to set email alerts
|

Pd-Catalyzed Decarboxylative Cycloaddition for the Synthesis of Highly Substituted δ-Lactones and Lactams

Abstract: An efficient palladium-catalyzed decarboxylative cycloaddition process of vinyl cyclic carbonates and vinyloxazolidinones for the synthesis of highly substituted δ-lactone and δ-lactam derivatives was developed. This protocol exhibits several unique characteristics, including broad substrate scope, good functional group tolerance, and operational convenience, which enables a regioselective access to a variety of lactone and lactam scaffolds in moderate to good yield. The redox-neutral catalytic system promotes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 59 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…also reported the synthesis of δ‐lactams by Rh‐catalyzed C−H activation/annulation method using N ‐pivaloyloxy acrylamides with unactivated alkenes [11] . In 2021, Gong and Yang reported palladium‐catalyzed decarboxylative cycloaddition of vinyl cyclic carbonates for the synthesis of these compounds [12] . Several asymmetric δ‐lactam synthesis have been also reported.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…also reported the synthesis of δ‐lactams by Rh‐catalyzed C−H activation/annulation method using N ‐pivaloyloxy acrylamides with unactivated alkenes [11] . In 2021, Gong and Yang reported palladium‐catalyzed decarboxylative cycloaddition of vinyl cyclic carbonates for the synthesis of these compounds [12] . Several asymmetric δ‐lactam synthesis have been also reported.…”
Section: Methodsmentioning
confidence: 99%
“…[11] In 2021, Gong and Yang reported palladium-catalyzed decarboxylative cycloaddition of vinyl cyclic carbonates for the synthesis of these compounds. [12] Several asymmetric δ-lactam synthesis have been also reported. In 2013, Chi et al reported organocatalytic enantioselective γaminoalkylation of unsaturated ester for the synthesis of δlactams.…”
mentioning
confidence: 99%
“…A Pd‐catalyzed decarboxylative cycloaddition of 5‐vinyl‐2‐oxazolidinones employing a CO atmosphere under balloon pressure was recently developed by Zhang and co‐workers for the construction of highly substituted δ ‐lactam derivatives 206 (Scheme 65). [106] This practical process features mild reaction conditions, broad substrate scope, and good functional‐group tolerance with both electron‐withdrawing and electron‐donating substituents on the aryl ring. Importantly, a gram‐scale decarboxylative cycloaddition reaction offered the expected lactam with a tetrasubstituted double bond with comparable yields.…”
Section: Ring‐opening Transformation Of 2‐oxazolidinonesmentioning
confidence: 99%
“…[17] We also have reported an efficient Pdcatalyzed domino decarboxylation/carbonylation/cyclization process of VECs for the synthesis of diverse lactones and lactams. [18] In recent years, we have designed practical and reliable methodology methods for the formation of highly functionalized skeletons. [19,20] We developed a Pd-catalyzed synthesis of spiroketal oxindoles from vinylethylene carbonates (VECs) with isatins through the in situ generation of a spiroketal system and quaternary stereocenter functionality (Scheme 1c).…”
Section: Introductionmentioning
confidence: 99%